Research spin-off firms: does the university involvement really matter? - Salvador, Elisa; Benghozi, Pierre-Jean (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Research spin-offs (RSOs) are considered as potential key opportunities for universities. This paper aims to contribute to the debate on RSOs through an examination of the relationship between these firms and their parent institute: the goal is to understand in which extent the university involvement could make the difference or not. Original empirical evidence on the Italian RSOs is provided by means of a questionnaire investigation, with a focus on companies that aroused more interest from their university and those that did not. Descriptive statistics is followed by a cluster and a factor analysis. Two main groups of RSOs are identified: open-oriented and autonomous-oriented. It seems that the strength of university interest towards a RSO has consequences on company orientation.